Gene loops function to maintain transcriptional memory through interaction with the nuclear pore complex - Tan-Wong, S; Wijayatilake, H; Proudfoot, N (Cold Spring Harbor Laboratory Press, 2009)
Inducible genes in yeast retain a "memory" of recent transcriptional activity during periods of short-term repression, allowing them to be reactivated faster when reinduced. This confers a rapid and versatile gene expression response to the environment. We demonstrate that this memory mechanism is associated with gene loop interactions between the promoter and 3' end of the responsive genes HXK1 and GAL1FMP27. The maintenance of these memory gene loops (MGLs) during intervening periods of transcriptional repression is required for faster RNA polymerase II (Pol II) recruitment to the genes upon reinduction, thereby facilitating faster mRNA accumulation. Notably, a sua7-1 mutant or the endogenous INO1 gene that lacks this MGL does not display such faster reinduction. Furthermore, these MGLs interact with the nuclear pore complex through association with myosin-like protein 1 (Mlp1). An mlp1Delta strain does not maintain MGLs, and concomitantly loses transcriptional memory. We predict that gene loop conformations enhance gene expression by facilitating rapid transcriptional response to changing environmental conditions.